Analysis Critical Control Point (CCP) in Frozen Surimi Production in PT. Bintang Karya Laut, Kabupaten Rembang, Propinsi Jawa Tengah - Nur Fais; Gunanti Mahasri (Journal of Marine and Coastal Science, 2019)
Indonesia has vast water area (5,8 million km2) as well as abundant fisheries production (10,83 million tones in 2010). This needs to be balanced with the proper processing of diversivication, one of wich is surimi. Surimi is intermediet product in the form of minced meat wich has undergone washing, pressing, and freezing. Surimi has inherent limitations prone to degradation affected by characteristics raw material as well as errors in the production process. Hazard analysis critical control point (HACCP) management system can be applied to prevent damage due to improper production process. One of the principles of hazard analysis critical control point (HACCP) is the analysis of the critical control poin (CCP),which focuses on hazard mitigation at the critical point of a production process. The methods used in the field practice is descriptive method. Data collection method involves collecting primary data and secondary. Primary data in the form of interviews, observation, and active participation. Surimi productions process in PT. Bintang Karya Laut consists of the receipt of raw materials, washing I, weeding, washing II, the separation of meat, leaching, filtering and pressing, mixing, printing and packaging, freezing, metal detecting, packing and labeling, and storage of frozen. Frozen surimi production in PT. Bintang Karya Laut is ± 7.500 tons/year of row material 30.000 tons. Based on hazard analysis, critical control point (CCP) on the production process of frozen surimi in PT. Bintang Karya Laut are on the three stages : receipt of raw materials, metal detection, and frozen storage. Problems that become obstacles in the process of analysis critical control point (CCP) in PT. Bintang Karya Laut is the limited tools to detect danger at any point of the critical control point (CCP).